ANALISIS KRIMINOLOGI KEJAHATAN PEMBUNUHAN BERENCANA OKNUM POLISI DI JAYAPURA - Sujud Sujud (Legal Standing : Jurnal Ilmu Hukum, 2021)
Murder is an inhuman crime, where the perpetrator of the crime kills with the intention of being planned in advance because it will kill other people's lives for a specific purpose, this crime is a crime of enmity between individuals and groups so that the victim is helpless, so the police investigator reveals his identity. Carefulness is needed. The problems discussed are what are the factors causing the crime of murder and how are the efforts to overcome the crime of murder. The research method used is normative juridical research. Data collection is based on literature study, based on the results of the research that the author has done, the factors that cause murder are internal and external factors. Internal factors, namely internal factors, and external factors, namely economic, environmental, and family factors. Efforts to tackle the crime of murder, namely penal and non-penal measures, are efforts to reduce the space for movement and opportunities for the committing of crimes. The suggestion in this research is that there is a need for cooperation between legal institutions and the government through police and military officers to prevent and cope with future premeditated murder, prosecutors and judges are requested to be able to prosecute and impose the maximum possible punishment on the perpetrators of the murder guided by the Criminal Code.